Determinasi Ketepatan Waktu Pelaporan Keuangan: Pengaruh Kinerja, Kepemilikan Institusional, dan Pergantian Auditor dengan Moderasi Komite Audit - Afdila Puspitasari; Suyanto Suyanto; Gustin Padwa Sari (Universitas Muhammadiyah Metro, 2026)
This study aims to provide empirical evidence regarding the effect of financial performance, institusional ownership and auditor turnover on the timeliness of financial reporting with the audit committee as a moderating variable. The sample determination used the purposive sampling method so that 192 samples of audited financial reports pf property and real estate companies were obtained. The data testing method in this study was logistic regression analysis with the SPSS 22 application. The results of this study indicate that financial performance proxied through ROA has a significant effect on the timeliness of financial reporting. While institusional ownership and auditor turnover do not affect the timeliness of financial reporting. The audit committee as a moderator is unable to moderate the influence between financial performance variables, institusional ownership and auditor turnover on the timeliness of financial reporting.